The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1212/wnl.55.4.604-b
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of vascular dementia from AD on neuropsychological tests

Abstract: To the Editor: Pradhan et al. 1 report five cases of Japanese encephalitis (JE) with typical parkinsonian features. Of 52 patients with JE, five were selected based on isolated lesions in the substantia nigra on MRI. We also reported a rat model of PD 2 induced by the JE virus, which revealed bradykinesia and predominant involvement of substantia nigra as the major pathologic changes. This parkinsonism model is made in rats infected with JE virus at 13 days after birth. We demonstrated that the susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Although several studies have attempted to identify neuropsychological patterns typical of VaD or AD, 97–104 few studies have addressed this issue in MD, but one study by Bowler et al, reported that neuropsychological characteristics of MD are more closely related to those of VaD than AD, suggesting an important role for the ischemic component of MD 105 …”
Section: Risk Factorsmentioning
confidence: 99%
“…Although several studies have attempted to identify neuropsychological patterns typical of VaD or AD, 97–104 few studies have addressed this issue in MD, but one study by Bowler et al, reported that neuropsychological characteristics of MD are more closely related to those of VaD than AD, suggesting an important role for the ischemic component of MD 105 …”
Section: Risk Factorsmentioning
confidence: 99%
“…A growing body of evidence suggests that a strong association between executive dysfunction and IADL impairment exists in patients with VaD due to small vessel disease [23][24][25][26]. Importantly, this relationship appears to be independent of dementia severity.…”
Section: Discussionmentioning
confidence: 99%
“…Executive dysfunction is arguably the most salient neuropsychological feature of VaD and has emerged as a reliable determinant of IADL impairment in demented elderly [23][24][25][26][27][28][29][30][31]. Executive functions include complex thinking abilities, mental flexibility/set shifting, and behavioral initiation and persistence.…”
Section: Neuropsychological Correlates Of Iadl Dysfunction In Vadmentioning
confidence: 99%
“…Memory loss, necessary to fulfil the NINDS-AIREN criteria, may be not present at the beginning of the disease, being predominant the executive deficits [12,13]. Moreover, in VCI there is no single, classical neurobehavioral and cognitive phenotype since vascular brain injury may affect any region of the brain.…”
Section: Diagnostic Criteriamentioning
confidence: 99%